2013
DOI: 10.1111/1567-1364.12120
|View full text |Cite
|
Sign up to set email alerts
|

Improved sake metabolic profile during fermentation due to increased mitochondrial pyruvate dissimilation

Abstract: Although the decrease in pyruvate secretion by brewer's yeasts during fermentation has long been desired in the alcohol beverage industry, rather little is known about the regulation of pyruvate accumulation. In former studies, we developed a pyruvate under-secreting sake yeast by isolating a strain (TCR7) tolerant to ethyl α-transcyanocinnamate, an inhibitor of pyruvate transport into mitochondria. To obtain insights into pyruvate metabolism, in this study, we investigated the mitochondrial activity of TCR7 b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
8
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(10 citation statements)
references
References 42 publications
2
8
0
Order By: Relevance
“…As succinic acid and malic acid are produced by the tricarboxylic acid (TCA) cycle within the mitochondria and amino acids such as branched-chain amino acids and proline are synthesized in the mitochondria (25,26), these results suggest that substances produced in the cytosol and the mitochondria contributed to the segregation of PC1 and the discrimination of chromosome XI aneuploids. This is consistent with our previous study showing that the pyruvate-underproducing strain TCR7 displayed an increase in mitochondrial activity and metabolic rate (19). As glucose contributed to the construction of PC2, we interpreted PC2 to be the component reflecting the fermentation abilities of the haploids.…”
Section: Genome Analysis Of Pyruvate-underproducing Sake Yeast Tcr7 Esupporting
confidence: 92%
See 1 more Smart Citation
“…As succinic acid and malic acid are produced by the tricarboxylic acid (TCA) cycle within the mitochondria and amino acids such as branched-chain amino acids and proline are synthesized in the mitochondria (25,26), these results suggest that substances produced in the cytosol and the mitochondria contributed to the segregation of PC1 and the discrimination of chromosome XI aneuploids. This is consistent with our previous study showing that the pyruvate-underproducing strain TCR7 displayed an increase in mitochondrial activity and metabolic rate (19). As glucose contributed to the construction of PC2, we interpreted PC2 to be the component reflecting the fermentation abilities of the haploids.…”
Section: Genome Analysis Of Pyruvate-underproducing Sake Yeast Tcr7 Esupporting
confidence: 92%
“…To circumvent this problem, pyruvate-underproducing sake yeasts have been developed by isolating mutants resistant to pyruvate analogues (16) or resistant to an inhibitor of the mitochondrial pyruvate transporter molecule (17); these strains are currently used in sake manufacturing in Japan (18). The latter type of strain was shown to have increased mitochondrial metabolism and activity (19). However, the genetic basis of its phenotype has not been elucidated.…”
mentioning
confidence: 99%
“…For example, it was reported that the mitochondrial activity of yeast used for brewing Japanese sake affected malate and succinate production during alcoholic fermentation (32,33). Moreover, Kyokai 7, yeast used for brewing Japanese sake, displayed greater the oxidative TCA cycle activity and the mitochondrial activity than the laboratory strain according to 13 C-MFA and mitochondrial morphology (22). These results supported that yeast used for brewing Japanese sake showed also the greater levels of TCA cycle flux than laboratory yeast in the low specific growth rate (dilution rate) condition in this study.…”
Section: Discussionmentioning
confidence: 99%
“…However, the Kyokai 6 strain showed lower yields of acetate and glycerol, and higher yield of ethanol. The former might be attributed to the enhanced expression of acetyl-CoA synthetase (ACS1) and cytosolic NADH oxidation activity in S. cerevisiae strains for Japanese sake brewing under aerobic conditions (21,22), while the latter may be related to the characteristics of Japanese sake brewing strains, which show higher ethanol productivity than that shown by laboratory strains of S. cerevisiae (23). In the case of the dilution rate of 0.06 h À1 , no ethanol production was observed for the Kyokai 6 strain, whereas S288C strains produced ethanol with yield of 13 mol/100 mol glucose À1 .…”
Section: Variation In Sam Production Levels Among S Cerevisiae Strainsmentioning
confidence: 99%
“…Moreover, we were the first to show that production of malic and succinic acids is affected by mitochondrial membrane potential and that malic acid is produced outside mitochondria during alcoholic fermentation. Furthermore, sake yeast strains that are relatively poor producers of pyruvate exhibit high mitochondrial metabolism (Agrimi et al, 2013). However, these studies did not determine whether the differences in fermentation profiles were caused by naturally occurring mutations in brewery yeasts that affect mitochondrial activities.…”
Section: Introductionmentioning
confidence: 99%